Effects of Progressive Strength Training on Bone Health and Functional Fitness in Older Adults Aged Sixty and Above - Istiqamah, Nurul; Sari, Wanda; Silviana, Vinny (ScieClouds Publishing, 2023)
The present research aims at evaluating the effectiveness of a 12-week progressive ST on bone and functional fitness of the older adults with limited evidence in the existing literature. In this experimental study, 100 sedentary elderly people who met the inclusion criteria were selected through purposive sampling and divided into two groups based on convenience sampling; experimental group n = 50 received supervised resistance training and the control group n = 50 continued with their normal daily activities with no exercise. BMD was measured by DXA at the lumbar spine, femoral neck, and the total hip. Osteocalcin and C-terminal telopeptide (CTX) were used also to determine bone formation and resorption rates. Basic and higher-level functional fitness was measured using the Timed Up and Go (TUG) test and the 30 second chair stand test. Significant results were noted in comparing the body composition, BMD, biomarkers of bone turnover, and functional fitness in the experimental group versus control group where p < 0.05 using pair sample t-test and two-way ANOVA. Taken together with prior research, these results offer strong confirmation of the value of strength training in building bone strength as well as increasing physical capabilities. In contrast to the previously mentioned studies this research encompasses a sample of older adults of different backgrounds, meaning the findings can enriched from a general perspective. This study highlights the need for broad integration of strength training in healthy aging framework for omorbidities of spine and fracture prevention along with functional dependency in elderly.